Extended Water Level Trends at Long‐Record Tide Gauges Via Moving Window Averaging and Implications for Future Coastal Flooding. Issue 10 (25th October 2021) - Devlin, Adam T.; Pan, Jiayi; Lin, Hui
Abstract: Quantifying the nature and patterns of sea level rise (SLR) is a critical challenge for the sustainability and resilience of coastal zones. Studies of SLR typically consider time‐averaged mean sea level (MSL) trends, however, coastal flooding is more sensitive to extended water level (EWL), which includes time‐variable components such as tides and seasonal variability. Here, we describe a new way to determine long‐term trends of peak extended water levels (PEWL) considering combined monthly averaged MSL and tidal range and their changes in linear rates and variability, which are compared to trends in mean extended water levels (MEWL) over moving 20‐year time windows at long‐period tide gauges over two epochs: century‐scale, and half‐century‐scale. Results show that a majority of locations exhibit different PEWL trends than MEWL trends in both epochs, and this difference has intensified in the past 50 years. There are strong regional coherencies observed: positive PEWL trends along western boundaries of basins (US Atlantic Coast, Japan, and Australia), and negative PEWL trends in most of Europe and the US Pacific Coast. Strong correlations to the Atlantic Multidecadal Oscillation and the Pacific Decadal Oscillation are also observed at many locations. Significant contributions from changes in tidal range and/or variability highlights the importance of considering multiple components of the water level spectrum beyond MSL. Our results are further analyzed in the context of IPCC projections to demonstrate that increased rates of PEWL may have additional implications for future flood levels at locations which have large projected increases in SLR. Plain Language Summary: Sea level rise is a critical concern for coastal locations and has been extensively studied. Most previous approaches rely on the analysis of mean sea level (MSL) trends over long time periods. These estimates, however, typically neglect the evolution of tides as well as the influence of changing short‐term (e.g., annual and seasonal) variability. Accurate assessments of potential future flood risks are better provided by the consideration of extended water levels (EWL), which includes MSL and tides, and the long‐term changes in peak extended water levels (PEWL), which allows examination of long‐term evolution in rates of MSL, tides, and annual or seasonal cycles. Our study uses 20‐year averaging of long‐record tide gauges to determine trends in PEWL. Results demonstrate that PEWL is increasing more rapidly than mean water levels in the Western Atlantic and Western Pacific, especially during the past 50 years. These trends may have serious implications for future increases in local flood levels. The recent shift in rates may be connected to large‐scale climate cycles, likely a consequence of global warming impacts such as increased glacial ice melt and warming oceans. Key Points: Extended water levels include mean sea level and tides and may be increasing faster than mean sea level alone Tidal evolution and the influence of annual variability may be a driver of extended water level increase Moving window averaging of peak extended water level trends can reveal locations where coastal flooding may become worse in the future